If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4y + 2(y + 2) = -32 Reorder the terms: 4y + 2(2 + y) = -32 4y + (2 * 2 + y * 2) = -32 4y + (4 + 2y) = -32 Reorder the terms: 4 + 4y + 2y = -32 Combine like terms: 4y + 2y = 6y 4 + 6y = -32 Solving 4 + 6y = -32 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 6y = -32 + -4 Combine like terms: 4 + -4 = 0 0 + 6y = -32 + -4 6y = -32 + -4 Combine like terms: -32 + -4 = -36 6y = -36 Divide each side by '6'. y = -6 Simplifying y = -6
| x/4-4=11 | | 8x^4-40x^2+80=0 | | 2(n+1)+3(n-1)=4n | | -18=6(x-4)-4x | | 16r^3-4r+10=0 | | 6x-16=1x+14 | | 48/-8= | | 26=-2v+4(v+7) | | 8-2(7)--5= | | 4.3+2.3x=7.1-1.9x | | 90(r-18)=10(13r+38) | | 9X-7x+5=31 | | 16k^2+40k+25=0 | | 2t+7=9 | | x-10/7=70 | | 132p-792=1716 | | -8+5x-2x=-26 | | 4/10X=3/5 | | -(x-2)-6.5x=2.5x+19 | | 82/3/21/12 | | (1.25)/(15/7) | | 5x^2-65x+200=0 | | 82/3/27/12 | | (2)(4)+5[6-(-2)]= | | 1.25/17/7 | | 4.9z+4.6=3.2z-22 | | 3x+10=-7x-50 | | 8x^2+5x=3x-2 | | 13-x/2=0 | | 14=-1(-1p+-8) | | y=-16t^2+55t+6 | | 107x-2x=6x+11 |